Intelligent Characterization of Lentil Genetic Resources: Evolutionary History, Genetic Diversity of Germplasm, and the Need for Well‐Represented Collections. Issue 5 (18th May 2021) - Guerra‐García, Azalea; Gioia, Tania; von Wettberg, Eric; Logozzo, Giuseppina; Papa, Roberto; Bitocchi, Elena; Bett, Kirstin E
Abstract: The genetic and phenotypic characterization of crops allows us to elucidate their evolutionary and domestication history, the genetic basis of important traits, and the use of variation present in landraces and wild relatives to enhance resilience. In this context, we aim to provide an overview of the main genetic resources developed for lentil and their main outcomes, and to suggest protocols for continued work on this important crop. Lens culinaris is the third‐most‐important cool‐season grain and its use is increasing as a quick‐cooking, nutritious, plant‐based source of protein. L. culinaris was domesticated in the Fertile Crescent, and six additional wild taxa ( L. orientalis, L. tomentosus, L. odemensis, L. lamottei, L. ervoides, and L. nigricans ) are recognized. Numerous genetic diversity studies have shown that wild relatives present high levels of genetic variation and provide a reservoir of alleles that can be used for breeding programs. Furthermore, the integration of genetics/genomics and breeding techniques has resulted in identification of quantitative trait loci and genes related to attributes of interest. Genetic maps, massive genotyping, marker‐assisted selection, and genomic selection are some of the genetic resources generated and applied in lentil. In addition, despite its size (∼4 Gbp) and complexity, the L. culinaris genome has been assembled, allowing a deeper understanding of its architecture. Still, major knowledge gaps exist in lentil, and a deeper understanding and characterization of germplasm resources, including wild relatives, is critical to lentil breeding and improvement. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Recording of lentil seed descriptors Basic Protocol 2 : Lentil seed imaging Basic Protocol 3 : Lentil seed increase Basic Protocol 4 : Recording of primary lentil seed INCREASE descriptors